2014
DOI: 10.1371/journal.pone.0089898
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Brain Damage, Synaptic Reorganization and NMDA Activation in a Model of Epileptogenic Cortical Dysplasia

Abstract: Whether severe epilepsy could be a progressive disorder remains as yet unresolved. We previously demonstrated in a rat model of acquired focal cortical dysplasia, the methylazoxymethanol/pilocarpine - MAM/pilocarpine - rats, that the occurrence of status epilepticus (SE) and subsequent seizures fostered a pathologic process capable of modifying the morphology of cortical pyramidal neurons and NMDA receptor expression/localization. We have here extended our analysis by evaluating neocortical and hippocampal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 84 publications
4
18
1
Order By: Relevance
“…3D3 , D 4 , arrows). As reported in our recent paper(Colciaghi et al, 2014) at chronic epilepsy stages we consistently found a progressive reduction of hippocampal volume (compareFig. 3A 1-4 with Fig.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…3D3 , D 4 , arrows). As reported in our recent paper(Colciaghi et al, 2014) at chronic epilepsy stages we consistently found a progressive reduction of hippocampal volume (compareFig. 3A 1-4 with Fig.…”
supporting
confidence: 87%
“…15 reported in epileptic MP rats (Colciaghi et al, 2014). However, the activation of the c-Jun pathway is not necessarily related to ongoing cell death.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, CYP treatment induced a significant swelling of the cell body in neurons of the DG and CA1 compared to the other cohorts. Past work (38) has documented hypertrophy of the soma associated with other neuropathological conditions, and current findings suggest that chemotherapy elicits a similar response. In each of the foregoing instances, stem cell grafting promoted the recovery of overall spine density and each of the CYP-depleted spine morphologies.…”
Section: Discussionsupporting
confidence: 60%
“…Potential risk factors include systemic complications (heart failure 20 and septic shock 21 ), malnutrition, 22,23 status epilepticus, 24,25 prolonged use of corticosteroids, 26 long-term exposure to various antiepileptic agents, 27,28 and propofol infusion syndrome. 29 Our patients with DCA developed more serious complications and required ventilatory support more frequently than did those without DCA.…”
Section: Discussionmentioning
confidence: 99%